2003
DOI: 10.1089/153623003772032853
|View full text |Cite
|
Sign up to set email alerts
|

In VitroandIn VivoDevelopmental Competence of Ovulated andIn VitroMatured Porcine Oocytes Activated by Electrical Activation

Abstract: The objective of this study was to evaluate the in vitro and in vivo developmental competence of parthenogenetic (parthenote) pig embryos derived from ovulated and in vitro matured (IVM) oocytes. A total of four experiments were carried out. These demonstrated that the mean blastocyst rates from stimulated ovulated and IVM pig oocytes were not significantly different (61% vs. 46%, p > 0.05) following in vitro culture. Both ovulated and IVM pig parthenotes were able to develop in vivo for 30 days. Parthenote fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…[28][29][30] Preimplantation development after parthenogenetic activation (PA) in the mouse is associated with abnormal DNA methylation pattern of imprinted genes compromising development to term, 21 a phenomenon that apparently also applies to the pig. 31 In order to refine the pig as a genetically modified biomedical model, it is of great importance to address the underlying epigenetic problems related to the use of assisted reproductive technologies in this species. 32 The main objectives of the present investigation were to optimize and validate the quantification of global DNA methylation normalized for the total DNA content and to use this methodology for analyzing the global level of DNA methylation in preimplantation porcine embryos developed in vivo (IV) and produced by IVF, SCNT and PA. the PA blastocysts had significantly (p < 0.05) higher levels.…”
Section: Dna Methylation Dna Content and Dnmt1 Localization In Porcimentioning
confidence: 99%
“…[28][29][30] Preimplantation development after parthenogenetic activation (PA) in the mouse is associated with abnormal DNA methylation pattern of imprinted genes compromising development to term, 21 a phenomenon that apparently also applies to the pig. 31 In order to refine the pig as a genetically modified biomedical model, it is of great importance to address the underlying epigenetic problems related to the use of assisted reproductive technologies in this species. 32 The main objectives of the present investigation were to optimize and validate the quantification of global DNA methylation normalized for the total DNA content and to use this methodology for analyzing the global level of DNA methylation in preimplantation porcine embryos developed in vivo (IV) and produced by IVF, SCNT and PA. the PA blastocysts had significantly (p < 0.05) higher levels.…”
Section: Dna Methylation Dna Content and Dnmt1 Localization In Porcimentioning
confidence: 99%
“…1,2,9,10 Murine androgenetic (AG) embryos with two sperm-derived genomes fail even earlier, with limited development of the embryo proper but often well-developed trophoblast, and reach at most early somite stages. 2,11,12 Parthenogenetic development in other mammalian species, including sheep, 13,14 cattle, 15 pig 16,17 and rabbit 18 can vary depending on the procedure used for activation of the oocyte, but does not proceed past early fetal stages, and developmental failure appears to be consistent with the stage when the conceptus begins to depend on the placenta. In species with delayed implantation, for example sheep and pig, PG fetuses can differentiate substantially and undergo organogenesis.…”
Section: Mammalian Uniparental Embryos: Origin and Developmentmentioning
confidence: 99%
“…In species with delayed implantation, for example sheep and pig, PG fetuses can differentiate substantially and undergo organogenesis. 13,16,17 Phenotypic similarities of PG conceptuses between species include growth retardation of the fetus (mouse, sheep, pig and rabbit, with the exception of sheep GG conceptuses 19 ), suggesting that mechanisms of genomic imprinting and effects of abnormal levels of imprinted gene products can be similar between mammalian species. 14 Some differences have been observed in respect to extraembryonic lineage development of maternally-derived conceptuses, which is severely hypotrophic in the mouse, 1 but not in sheep 19 or in rabbit.…”
Section: Mammalian Uniparental Embryos: Origin and Developmentmentioning
confidence: 99%
“…Previous studies have indicated that both the maternal and paternal genomes were essential for normal embryogenesis, and a lack of either could result in failed embryonic development (McGrath and Solter, 1984). Parthenogenetic (PA) embryos contain exclusively maternal genomes, and death occurs at gestational days 12, 21, 28, and 30 in rabbits, sheep, pigs and cattle, respectively (Zhu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%